A passion to preserve : gay men as keepers of culture - Fellows, Will (UPCC book collections on Project MUSE., 2004)
From large cities to rural communities, gay men have long been impassioned pioneers as keepers of culture: rescuing and restoring decrepit buildings, revitalizing blighted neighborhoods, saving artifacts and documents of historical significance. This penchant to preserve, though widely observed, is typically ignored or dismissed as a stereotypical gay cliché, even by many gay men themselves. This book explores this authentic and complex dimension of gay men's lives by profiling early and contemporary preservationists from throughout the United States, including oral histories collected by Fellows. This eye-opening book illuminates neglected facets of what it means to be gay and highlights contributions to the larger culture that gays are exceptionally inclined to make.--From publisher description.